Energetic and exergetic performance of a solar flat-plate collector working with cu nanofluid - Shamshirgaran, S. (American Society of Mechanical Engineers (ASME), 2018)
The evaluation of the performance and characteristics of a solar flat-plate collector (FPC) are reported for domestic and industrial requirements in the existing literature. A computer code was developed using MATLAB to model and evaluate the energetic and exergetic performance of a nanofluid-based FPC for steady-state and laminar conditions. The analysis was performed using practical geometry data, especially the absorber emittance, for a standard collector. Linear pressure losses in manifolds were taken into account, and a more accurate exergy factor corresponding to a correct value of 5770 K for the sun temperature was employed. The results demonstrate that copper-water nanofluid has the potential to augment the internal convection heat transfer coefficient by 76.5, and to enhance the energetic efficiency of the collector from 70.3 to 72.1 at 4 volume concentration, when compared to the values with water. Additionally, it was revealed that copper nanofluid is capable of increasing the collector fluid's outlet temperature and decreasing the absorber plate's mean temperature by 3 K. The addition of nanoparticles to the water demonstrated a reduction in the total entropy generation by the solar FPC. Furthermore, increasing the nanoparticle size reflected a reduction in the overall performance of the solar collector. Copyright Â© 2018 by ASME.